Design-based research in the context of transitioning to VET: Developing interventions through research-practice collaboration - Brahm, Taiga (EDeR. Educational Design Research, 2017)
The transition from school to vocational education and training (VET) is becoming more difficult for an increasing number of adolescents. Despite the growing significance of this phase, the- re is hardly any research regarding interventions targeting stu- dents’ resilience, especially with regard to their capacity to join the labour market. This paper aims at describing the research process of developing three different interventions in coopera- tion with a number of practitioners who teach in so-called in- terim solutions. The goal of the paper is, thus, to illustrate how design-based research (DBR) can be conducted in the context of vocational education. The comprehensive three-cycle develop- ment of three interventions with the aim of fostering students’ conflict management competence, attribution and self-efficacy will be used as a single case study to illustrate a complex DBR project. Each step in the design-research process will be reflec- ted, resulting in a discussion of the possibilities and obstacles of combining formative and summative evaluation in the DBR process.